DEVELOPMENT OF SMART ASSET DATABASE SYSTEM - Rosli, Mas Iliani (UNIVERSITI TEKNOLOGI PETRONAS, 2014)
The urgency of the asset management rise when the needs of effective and efficient agenda to build an information building database become vital to the shareholder and owner of the building as the cost of maintenance and repairs are overly in the high edge for the organization. The major issue with the asset management is the lack of latest and accurate information about the asset over the years. There is no advanced management system to organize and maintain the information the asset. Thus, in order to reduce maintenance and repairs costs of the asset as well as to deliver effective and efficient asset management system in the organization, the objective of this study is to develop the information database of the building’s asset. The usage of laser scanner device as data collection and data processing in the asset management has come out as trend that gives fastest exact 3D modeling result that later will represent as the location of the asset. Furthermore, the integration Geographic Information System (GIS) into asset management has proven over the years the effectiveness and efficiency that can assist organization to track location, condition as well as analyze, manage and display information of the asset. In this study, the implementation of laser scanner technology and GIS will be used vastly in the computer laboratory in order to create the database information and yet to achieve effective asset management system.